Comparative Study Of Ct And 1.5 Tesla Mri In Quantitative Estimation Of Bone Mineral Density In Lumbar Spine - Ishant, Ishant; Kumar, Raushan (Journal of Neonatal Surgery, 2025)
The effectiveness of 1.5 Tesla magnetic resonance imaging (MRI) and quantitative computed tomography (QCT) for determining bone mineral density (BMD) in the lumbar spine of 44 patients (22 males, 22 females; mean age 46.02 ± 11.14 years) from Western Uttar Pradesh was compared in this prospective cross-sectional study, which was carried out at Teerthanker Mahaveer Hospital and Research Centre in Moradabad, India. Hounsfield Units (HU), QCT-derived BMD, and MRI signal intensities (T1-weighted, T2-weighted, gradient echo) among the L1–L5 vertebrae were among the measurements. Significant age-related differences (p < 0.05) were noted in T1, T2, HU, and QCT-BMD at particular lumbar levels, but no significant gender differences were reported in imaging parameters or BMD (p > 0.05). The sensitivity of MRI to bone marrow changes was demonstrated by Pearson correlation analysis, which revealed negative correlations between T1/T2 signal intensities and QCT-BMD and positive correlations between HU and QCT-BMD. 50% gender prediction accuracy was attained via binary logistic regression (100% for females, 0% for males). Despite drawbacks such geographical bias and small sample size, the results demonstrate MRI's potential as a radiation-free substitute for DEXA and validate CT's dependability for BMD evaluation. To improve diagnostic accuracy, future research should investigate larger cohorts and more sophisticated MRI techniques.